2008
DOI: 10.1037/0096-1523.34.4.790
|View full text |Cite
|
Sign up to set email alerts
|

Set-size effects for identification versus localization depend on the visual search task.

Abstract: In both behavior and neuroscience research, it is debated whether the processing of identity and location is closely bound throughout processing. One aspect of this debate is the possibly privileged processing of identity or location. For example, processing identity may have unlimited capacity, while processing location does not. The authors have investigated the possibility of such privileged processing by measuring set-size effects for a variety of identification and localization tasks. In particular, set-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 87 publications
2
27
0
Order By: Relevance
“…Numerous studies have investigated whether or not detection, localization, and recognition can be dissociated experimentally in visual search tasks or change detection tasks. Some of these studies found a dissociation of detection, localization, or recognition (Treisman & Gelade, 1980;Treisman & Gormican, 1988;Dukewich & Klein, 2009;Ghorashi et al, 2010;Busch et al, 2010a;Busch et al, 2010b;Schneider & Wascher, 2013;Chan & Hayward, 2009;Watanabe, 2003;Wolfe et al, 2006;Agostinelli et al, 1986;Becker et al, 2000;Turatto & Bridgeman, 2005;Hughes et al, 2012) while others found them to be similar (Luck & Vogel, 1997;Green, 1992;Joseph et al, 1997;Busey & Palmer, 2008;Zehetleitner & Müller, 2010) or found recognition to be conditional upon localization Donk and Meinecke (2001). Thus, whether target detection in visual search for static patterns can occur in the absence of localization or object recognition is still debated.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated whether or not detection, localization, and recognition can be dissociated experimentally in visual search tasks or change detection tasks. Some of these studies found a dissociation of detection, localization, or recognition (Treisman & Gelade, 1980;Treisman & Gormican, 1988;Dukewich & Klein, 2009;Ghorashi et al, 2010;Busch et al, 2010a;Busch et al, 2010b;Schneider & Wascher, 2013;Chan & Hayward, 2009;Watanabe, 2003;Wolfe et al, 2006;Agostinelli et al, 1986;Becker et al, 2000;Turatto & Bridgeman, 2005;Hughes et al, 2012) while others found them to be similar (Luck & Vogel, 1997;Green, 1992;Joseph et al, 1997;Busey & Palmer, 2008;Zehetleitner & Müller, 2010) or found recognition to be conditional upon localization Donk and Meinecke (2001). Thus, whether target detection in visual search for static patterns can occur in the absence of localization or object recognition is still debated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the frequency of such processing is much higher than expected from previous experiments on humans, or indeed the present study. More recently, using human observers, we showed (14, 15) that visual search tasks might be processed periodically by attention at low frequencies (5)(6)(7)(8)(9)(10). This discrepancy between our results and Buschman and Miller's results (24) might be due to different factors, such as the use of nonhuman primates, the recording of single neurons, or the intrinsic difficulty of the search task.…”
Section: Discussionmentioning
confidence: 99%
“…As detailed below, the unlimited-capacity models predict equivalence between the simultaneous and sequential conditions, while the fixed-capacity models predict equivalence between the repeated and sequential conditions. The specific models underlying these predictions are detailed in the appendix of Scharff et al (in press; see also Busey & Palmer, 2008, for a discussion of how to account for task variations). Unlimited capacity model Fig.…”
Section: Methodsmentioning
confidence: 99%
“…They found that out of three difficult visual search tasks (feature, spatial conjunction, and feature conjunction), one showed evidence of being limited capacity (spatial conjunction), and the other two did not. For another example, Palmer (1994), Palmer et al (2000), and Busey and Palmer (2008) manipulated both set size and the difficulty of a discrimination task and found that accuracy at all levels of difficulty was fit well by the same unlimited-capacity model. In sum, several studies have shown that capacity does not depend on task difficulty.…”
Section: Task Difficultymentioning
confidence: 99%